Realization of affiliation goals, interpersonal identity development, and well-being: effects of the implicit affiliation motive among German and Zambian adolescents - Hofer, Jan; Busch, Holger; Menon, Anitha (Frontiers in Psychology, 2024)
Introduction Across various cultural contexts, success in goal realization relates to individuals’ well-being. Moreover, commitment to and successful pursuance of goals are crucial when searching for a meaningful identity in adolescence. However, individuals’ goals differ in how much they match their implicit motive dispositions. We hypothesized that successful pursuance of affiliation goals positively relates to commitment-related dimensions of interpersonal identity development (domain: close friends) that, in turn, predict adolescents’ level of well-being. However, we further assumed that the links between goal success and identity commitment are particularly pronounced among adolescents who are characterized by a high implicit affiliation motive. Methods To scrutinize the generalizability of the assumed relationships, data were assessed among adolescents in individualistic (Germany) and collectivistic (Zambia) cultural contexts. Results Regardless of adolescents’ cultural background, we found that commitment-related dimensions of interpersonal identity development mediate the link between successful attainment of affiliation goals and well-being, particularly among adolescents with a pronounced implicit affiliation motive; that is, the strength of the implicit affiliation motive moderates the association between goal success and identity commitment. Conclusion We discuss findings concerning universal effects of implicit motives on identity commitment and well-being.